Espaços públicos abertos e o usufruto da paisagem : 1860 a 1916, Vitória (ES) - Bellini, Anna Karine de Queiroz Costa (2014)
The usage of public areas and the apprehension of ‘the townsman’s gaze’ over Vitória city, especially concerning his impressions over the local landscape from 1860 through 1916, are the prime object of this work. The methodology was particularly guided by